Long term mortality after severe starvation during the siege of Leningrad: prospective cohort study - Sparén, Pär (BMJ Publishing Group Ltd., 2004)
Objectives To determine whether starvation during periods of increased growth after birth have long term health consequences. Design Analysis of cardiovascular risk factors and mortality in a longitudinal follow up after the 1941-4 siege of Leningrad. Mortality measured from 1975 up to the end of 1999. Setting St Petersburg, Russia (formerly Leningrad). Participants 5000 men born 1916-35 who lived in Leningrad, randomly selected to take part in health examinations in 1975-7. Of the 3905 men who participated, a third had experienced the siege. Main outcome measures Relative risk of ischaemic heart disease and mortality from stroke by siege exposure. Odds ratios and means for several cardiovascular risk factors. Results Three to six decades after the siege, in men who experienced the siege around the age of puberty blood pressure was raised (mean difference in systolic 3.3 mm Hg, in diastolic 1.3 mm Hg) as was mortality from ischaemic heart disease (relative risk 1.39, 95% confidence interval 1.07 to 1.79) and stroke (1.67, 1.15 to 2.43), including haemorrhagic stroke (1.71, 0.90 to 3.22). The effect on mortality was partly mediated via blood pressure but not by any other measured biological, behavioural, or social factor. Conclusions Starvation, or accompanying chronic stress, particularly at the onset of or during puberty, may increase vulnerability to later cardiovascular disease.